Astragalus Extract Mixture HT042 Improves Bone Growth, Mass, and Microarchitecture in Prepubertal Female Rats: A Microcomputed Tomographic Study. (10th May 2017) - Song, Jungbin; Lee, Sung Hyun; Lee, Donghun; Kim, Hocheol
Abstract : Astragalus extract mixture HT042 is a standardized multiherbal mixture comprising Astragalus membranaceus, Eleutherococcus senticosus, and Phlomis umbrosa, which has proven to promote children's height growth. The aim of this study was to investigate the effects of HT042 on longitudinal bone growth, bone mass, and bone microstructure in growing rats using a high-resolution microcomputed tomography system. Four-week-old female rats were fed an HT042-containing diet for 2 weeks. Tibial length was measured at baseline and weekly in vivo . At the end of the study, volumetric bone mineral density (vBMD) and microarchitectural parameters were estimated in the trabecular and cortical bone of the tibia. Tibial length gain was significantly increased by HT042 compared to that reported with the control diet. In the proximal tibial metaphysis, HT042-treated rats had significantly higher trabecular vBMD, bone volume fraction, and trabecular number and lower trabecular separation, trabecular pattern factor, and structure model index values than control rats did. Total cross-sectional area and bone area of the cortical bone in the tibial diaphysis also increased. These findings suggest that HT042 increases longitudinal bone growth rate, improves trabecular bone mass, and enhances the microarchitecture of trabecular and cortical bone during growth.